Inter and Intra-Culture-Based Group Discussion to Promote Learning Autonomy in A Bicultural Class - Erna Iftanti (JEELS (Journal of English Education and Linguistics Studies), 2019)
Learning as a systematic change in knowledge, insights, behavior, and motivation occurs either in-classroom or out-of-classroom context. However, for bicultural class consisting of Indonesian and Thai EFL students in Indonesian context, to achieve such goals of learning is challenging, since the EFL students staying in such a class comprising those from two different cultural backgrounds faced some underlying learning problems. Therefore, to establish learning autonomy is significant. This article is then aimed at exploring inter and intra-culture-based group discussion which proved to be able to promote their learning autonomy. This research conducted qualitatively through observation, interview, and questionnaire revealed that the learning problems found in a bicultural class i.e. learning readiness, learning style, learning habits, and motivation can be solved by building and implementing both inter and intra-culture-based group discussion conducted in and outside classroom settings. This finding can be considered as important insight to create EFL students’ learning autonomy which contributes to prevent them from encountering learning problems in a bicultural class so that the EFL learning goals can be better achieved.